Reduced hippocampus and amygdala volumes in antisocial personality disorder - Kaya, Suheda; Yildirim, Hanefi; Atmaca, Murad (Elsevier Sci Ltd, 2020)
In the present paper, we aimed to investigate hippocampus and amygdala volumes in a group of patients with antisocial personality disorder and hypothesized that hippocampus and amygdala volume alterations would be observed. It was measured hippocampus and amygdala volumes of twenty patients with antisocial personality disorder and those of healthy control subjects. We found that both sides of hippocampus and amygdala volumes of patients with antisocial personality disorder were statistically significantly reduced compared to those healthy control subjects, and observed statistically important correlations between the left and right and left hippocampus and left amygdala volumes, and age, some results on scale scores. Consequently, the present study suggest that hippocampus and amygdala volumes of patients with antisocial personality disorder had abnormally smaller than those of healthy control subjects, considering that these abnormalities might be associated with at least some clinical features of antisocial personality disorder. However, longitudinal studies are needed to assess causality of this relationship. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Hippocampus; Amygdala; Antisocial personality disorder; Volumes